Construction of a 2D/2D g-C3N4/rGO hybrid heterojunction catalyst with outstanding charge separation ability and nitrogen photofixation performance via a surface protonation process. Issue 31 (9th March 2016) - Hu, Shaozheng; Zhang, Weidong; Bai, Jin; Lu, Guang; Zhang, Lei; Wu, Guang
Abstract : Heterojunction catalyst PCN/rGO with effective interfacial contact by incorporating reduced graphene oxide and protonated g-C3 N4 and outstanding nitrogen photofixation ability was synthesized via a electrostatic self-assembly strategy. Abstract : In this work, we report a 2D/2D hybrid heterojunction photocatalyst (PCN/rGO) with effective interfacial contact by incorporating reduced graphene oxide (rGO) and protonated g-C3 N4 (PCN) synthesized via a novel electrostatic self-assembly strategy, followed by an ethylene glycol reduction process. The GCN/rGO obtained by incorporating reduced graphene oxide (rGO) and g-C3 N4 without protonation (GCN) has also been prepared for comparison. PCN/rGO(0.2), with the mass ratio rGO/PCN of 0.2, exhibits the highest nitrogen photofixation performance under visible light. The NH4 + generation rate for PCN/rGO(0.2) is 42.4, 8.3 and 3.7 times higher than that of GCN, PCN and GCN/rGO(0.2). This is ascribed to the addition of rGO with PCN in a controlled ratio as well as sufficient interfacial contact by the electrostatic self-assembly process between rGO and PCN across the PCN/rGO heterojunction, for efficient charge transfer to suppress the recombination of electron–hole pairs, as evidenced by the zeta potential, XPS and PL studies. In addition, compared with GCN/rGO(0.2), the stronger interaction caused by the electrostatic attractive forces exists between PCN and rGO, leading to a better catalytic stability of PCN/rGO(0.2). This work opens up an effective way to prepare the heterojunction catalyst by incorporating two components with different surface charges.